EDUKASI PENCEGAHAN KECELAKAAN KERJA PADA PETUGAS KESEHATAN DI RSI KARAWANG - Yuliana, Chaerani Tri; Darmawan, Wendi; Jumaedi, Jumaedi; Muhidin, Muhidin; Widhiantika, Wieke (E-Amal: Jurnal Pengabdian Kepada Masyarakat, 2024)
The community service program themed "Work Accident Prevention Education Healthcare Workers at RSI Karawang" aims to improve the knowledge, attitudes, and skills of healthcare workers in implementing occupational health and safety (OHS) practices. This program involved a series of activities such as preliminary surveys, the preparation of educational modules, focused group discussions (FGD), training in the use of personal protective equipment (PPE), as well as pre-test and post-test evaluations. The results of the program showed a 35% increase in knowledge, improved compliance with PPE use from 40% to 75%, and enhanced ability to identify risks and active participation from healthcare workers. These findings indicate that participatory education programs with hands-on practice are effective in raising awareness and commitment to workplace accident prevention among healthcare workers. This program has the potential to serve as a model for implementation in other hospitals to create a safer and more productive work environmentfor